Recurrent chromosomal imbalances provide selective advantage to human embryonic stem cells under enhanced replicative stress conditions. Issue 4 (9th January 2021) - Mus, Liselot M.; Van Haver, Stéphane; Popovic, Mina; Trypsteen, Wim; Lefever, Steve; Zeltner, Nadja; Ogando, Yudelca; Jacobs, Eva Z.; Denecker, Geertrui; Sanders, Ellen; Van Neste, Christophe; Vanhauwaert, Suzanne; et al.
Abstract: Human embryonic stem cells (hESCs) and embryonal tumors share a number of common features, including a compromised G1/S checkpoint. Consequently, these rapidly dividing hESCs and cancer cells undergo elevated levels of replicative stress, inducing genomic instability that drives chromosomal imbalances. In this context, it is of interest that long‐term in vitro cultured hESCs exhibit a remarkable high incidence of segmental DNA copy number gains, some of which are also highly recurrent in certain malignancies such as 17q gain (17q+). The selective advantage of DNA copy number changes in these cells has been attributed to several underlying processes including enhanced proliferation. We hypothesized that these recurrent chromosomal imbalances become rapidly embedded in the cultured hESCs through a replicative stress driven Darwinian selection process. To this end, we compared the effect of hydroxyurea‐induced replicative stress vs normal growth conditions in an equally mixed cell population of isogenic euploid and 17q + hESCs. We could show that 17q + hESCs rapidly overtook normal hESCs. Our data suggest that recurrent chromosomal segmental gains provide a proliferative advantage to hESCs under increased replicative stress, a process that may also explain the highly recurrent nature of certain imbalances in cancer. Abstract :